Characteristics and Development Context of Engineering Universities in Vietnam - Tuan Anh, Vu; Huy, Nghiem Xuan; Thuong, Le Thi (VNU Journal of Science: Education Research; Vol 34 No 1DO - 10.25073/2588-1159/vnuer.4110, 2018)
The OECD (The Organization for Economic Co-operation and Development) reports show that science and technology play a significant role in socio-economic development. In this trend, education and training in the field of engineering and technology are crucial in forming and developing a labour force for adapting to the increasingly science and technology-powered context. Those countries who are undertaking suitable policies in engineering education and training have obtained remarkable development. In Vietnam, engineering education and training has caught on that trend via the increasing number of engineering universities. However, these higher education institutions would be only successful if receiving adequate attention in terms of development policies and investment. This paper aims at investigating the current status of engineering universities and proposing some recommendations for the development of this higher education section.